PENGARUH BAURAN PEMASARAN TERHADAP KEPUTUSAN KONSUMEN DALAM PEMBELIAN PESTISIDA DI UD. AGRIMART SEJAHTERA KOTA PANGKALAN KERINCI KABUPATEN PELALAWAN - Ari Sumantri; Susy Edwina; Eliza ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
This research aims to: (1). Determine the marketing mix that influence the consumers’ decisions in purchasing pesticides at UD. Agrimart Sejahtera in Pangkalan Kerinci. (2). Determine the constraints faced by UD. Agrimart Sejahtera in marketing the pesticides products.  In this research, 50 respondents has been selected through purposive sampling that would be interviewed, then analyzed descriptively and used likert scale. To answer the first goal, it has been analyzed descriptively and used likert scale. To answer the second goal, it has been done through interview at UD. Agrimart Sejahtera in Pangkalan Kerinci. The result of the research shows: (1). Overall the consumers’ decision in purchasing the pesticides at UD. Agrimart Sejahtera got an average value 195.12 that was included in “agree” categories, the consumers were agree with the marketing mix exsisted at UD. Agrimart Sejahtera with variable products, prices, places, promotions and services. (2). The constraints faced by UD. Agrimart Sejahtera: (a). Constraints in limiting some pesticides product brand from several distributors. (b). Price fluctuations constraints from distributors. (c). Promotion constraints.   Keywords:Marketing mix, buying decision, pesticide product